Production of diverse brGDGTs by Acidobacterium Solibacter usitatus in response to temperature, pH, and O2 provides a culturing perspective on brGDGT proxies and biosynthesis. Issue 1 (23rd September 2022) - Halamka, Toby A.; Raberg, Jonathan H.; McFarlin, Jamie M.; Younkin, Adam D.; Mulligan, Christopher; Liu, Xiao‐Lei; Kopf, Sebastian H.
Abstract: Branched glycerol dialkyl glycerol tetraethers (brGDGTs) are bacterial membrane lipids that are frequently employed as paleoenvironmental proxies because of the strong empirical correlations between their relative abundances and environmental temperature and pH. Despite the ubiquity of brGDGTs in modern and paleoenvironments, the source organisms of these enigmatic compounds have remained elusive, requiring paleoenvironmental applications to rely solely on observed environmental correlations. Previous laboratory and environmental studies have suggested that the globally abundant bacterial phylum of the Acidobacteria may be an important brGDGT producer in nature. Here, we report on experiments with a cultured Acidobacterium, Solibacter usitatus, that makes a large portion of its cellular membrane (24 ± 9% across all experiments) out of a structurally diverse set of tetraethers including the common brGDGTs Ia, IIa, IIIa, Ib, and IIb. Solibacter usitatus was grown across a range of conditions including temperatures from 15 to 30°C, pH from 5.0 to 6.5, and O2 from 1% to 21%, and demonstrated pronounced shifts in the degree of brGDGT methylation across these growth conditions. The temperature response in culture was in close agreement with trends observed in published environmental datasets, supporting a physiological basis for the empirical relationship between brGDGT methylation number and temperature. However, brGDGT methylation at lower temperatures (15 and 20°C) was modulated by culture pH with higher pH systematically increasing the degree of methylation. In contrast, pH had little effect on brGDGT cyclization, supporting the hypothesis that changes in bacterial community composition may underlie the link between cyclization number and pH observed in environmental samples. Oxygen concentration likewise affected brGDGT methylation highlighting the potential for this environmental parameter to impact paleotemperature reconstruction. Low O2 culture conditions further resulted in the production of uncommon brGDGT isomers that could be indicators of O2 limitation. Finally, the production of brGTGTs (trialkyl tetraethers) in addition to the previously discovered iso‐C15‐based mono‐ and diethers in S. usitatus suggests a potential biosynthetic pathway for brGDGTs that uses homologs of the archaeal tetraether synthase (Tes) enzyme for tetraether synthesis from diethers.